Efficacy of the educational program “For responsible sexuality” on the knowledge of sexuality in adolescents of the fifth year of secondary school of the Adventist Educational Institution Puno, Puno, 2016 - Alarcón Rodriguez, Raquel (2020)
Objective: Was to determine the effectiveness of the educational program “For responsible sexuality” on the knowledge of sexuality in adolescents of the fifth year of secondary school of the Adventist School Puno- Puno, 2016. Methodology: The study was quantitative, quasi-experimental design, applying a Pre and post test. The sample consisted of 51 adolescents aged 14 to 17, distributed in two groups randomly: experimental group and control group. A questionnaire on sexuality in adolescents was applied to measure the level of knowledge. The results of the “control group”: in the pre-test a 48.1% low level and 44.4% medium level, in the post test a result was shown similar to 48.1% at the low level and 48.1% at the medium level. Resulted: In the “experimental group” before the application of the program 50.0% presented a medium level and 33.3% a low level, only 16.7% a high level, in the post test the knowledge of adolescents was they increased to 83.3% with a high level and 16.7% a medium level, with a significant difference compared to the control group. Conclusion: that at a level of significance of (sig =, 000), the educational program was effective in improving knowledge about sexuality in adolescents.